1996
DOI: 10.1063/1.363229
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial evolution of C2 in laser induced plasma from graphite target

Abstract: Laser ablation of graphite has been carried out using 1.06 m radiation from a Q-switched Nd:YAG laser and the time of flight distribution of molecular C 2 present in the resultant plasma is investigated in terms of distance from the target as well as laser fluences employing time resolved spectroscopic technique. At low laser fluences the intensities of the emission lines from C 2 exhibit only single peak structure while beyond a threshold laser fluence, emission from C 2 shows a twin peak distribution in time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…The absorption due to inverse bremsstrahlung, negligibly small at low laser intensities increases exponentially with increasing laser intensity beyond threshold value [23]. The emission intensity of ionized species increases drastically above the threshold laser intensity [13,41]. Once ions and electrons are produced, one can have neutral carbon atoms by three body recombination process of the type C þ þ e þ e ¼ C þ e. However, in the vicinity of the target the temperature of the plume is high and it is the collision processes, C þ e ¼ C þ þ e þ e that predominate over the recombination and hence we see excited C 2 away from the target.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption due to inverse bremsstrahlung, negligibly small at low laser intensities increases exponentially with increasing laser intensity beyond threshold value [23]. The emission intensity of ionized species increases drastically above the threshold laser intensity [13,41]. Once ions and electrons are produced, one can have neutral carbon atoms by three body recombination process of the type C þ þ e þ e ¼ C þ e. However, in the vicinity of the target the temperature of the plume is high and it is the collision processes, C þ e ¼ C þ þ e þ e that predominate over the recombination and hence we see excited C 2 away from the target.…”
Section: Resultsmentioning
confidence: 99%
“…In these data, it is apparent that a relationship exists between the ionic emission spectra in the plumes under study and the degree of vibrational emission observed in the same plasma [35]. For the runs at 5¥10 The formation of dimers can happen by one of two situations: either the dimers are formed in the presence of ions in densities proportional to the ion density, or a similar density of ions to dimers leaves the target surface initially [36]. It is unlikely that a significant number of dimers is emitted from the target surface because the bond energy of Si 2 is only about 1 eV [37], as compared with the first ionization energy of atomic silicon of 8.1 eV.…”
Section: Figure 15mentioning
confidence: 97%
“…Another result was the detection of C 2 molecular species in the nitrogen atmosphere, evidenced from characteristic emission lines belonging to the Swan A 3 Π g -X '3 Π u system. Detection of C 2 molecules is related to plume thermalization caused by collisions with background nitrogen molecules, promoting recombination of C to form C 2 [11]. Fullerenelike CNx films have predominantly graphite-like structures and require sp 2 electron hybridization.…”
Section: Resultsmentioning
confidence: 99%